2019
DOI: 10.3389/fpsyg.2019.00297
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects of Life Events and Hair Cortisol on Perceived Stress, Anxiety, and Depressive Symptoms Among Chinese Adolescents: Testing the Differential Susceptibility and Diathesis-Stress Models

Abstract: The differential susceptibility model and the diathesis-stress model on the interaction effect between the individuals’ traits and environmental factors will be conducive to understand in depth whether the psychophysiological traits are the risk factors of child development. However, there is no study focusing on the activity of the hypothalamic-pituitary-adrenal (HPA) axis. We examined whether the HPA activity serves as a physiological marker of the differential susceptibility model or the diathesis-stress mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 62 publications
2
12
0
2
Order By: Relevance
“…Nurses with low stress reactivity not only showed higher professional inefficacy than those with high stress reactivity under high job stress due to low expression of naturally felt emotions but also showed lower professional inefficacy under low job stress due to high expression of naturally felt emotions. These results together with the above-mentioned previous findings on the interaction between stress reactivity and stressful environmental factors in predicting adolescents' psychological adaptations [ 23 , 37 , 38 , 40 ] supported the differential susceptibility model. It implied that stress reactivity might be the plasticity factor for Chinese nurses' emotional exhaustion, depersonalization, and professional inefficacy in MBI burnouts.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Nurses with low stress reactivity not only showed higher professional inefficacy than those with high stress reactivity under high job stress due to low expression of naturally felt emotions but also showed lower professional inefficacy under low job stress due to high expression of naturally felt emotions. These results together with the above-mentioned previous findings on the interaction between stress reactivity and stressful environmental factors in predicting adolescents' psychological adaptations [ 23 , 37 , 38 , 40 ] supported the differential susceptibility model. It implied that stress reactivity might be the plasticity factor for Chinese nurses' emotional exhaustion, depersonalization, and professional inefficacy in MBI burnouts.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, nurses with higher stress reactivity are also more susceptible to the context related to job demands and are more easily affected by job stress, such as stressful emotional labor demands in work environments. This explanation obtains the support from previous findings demonstrating that individuals with high stress reactivity are more likely to show more maladaptive outcomes (e.g., lower prosocial behaviors and more anxiety symptoms) under adverse environments but more adaptive outcomes under supportive environments [ 23 , 37 , 38 , 40 ]. However, the explanation is held for associations of surface acting and deep acting with emotional exhaustion and depersonalization, but not for the association between the expression of naturally felt emotions and professional inefficacy.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Previous studies had demonstrated that stress reactivity could moderate the relationship between environmental factors and adolescents' psychological adaptations (Wiel et al, 2004;Obradovi et al, 2010Obradovi et al, , 2015Owens et al, 2018;Xu et al, 2019) and the relationship between emotional labor and job burnouts (Deng et al, 2020). Thus, we hypothesized that hair cortisol levels (or stress reactivity) could moderate the relationship between environmental factors and work-related outcomes among Chinese nurses.…”
Section: The Present Studymentioning
confidence: 94%